Penerapan pembelajaran berbasis permainan untuk meningkatkan keterampilan sosial pada anak usia dini di Era Digital - Khusniyah, Syarifatul (Maliki Interdisciplinary Journal, 2024)
Game-based learning has become one of the effective methods in enhancing social skills in early childhood. By utilizing digital technology, this method can become more engaging and effective. This study aims to analyze the impact of implementing digital game-based learning on the social skills of early childhood. This research uses a qualitative approach with case study methods in several kindergartens in Indonesia. The results show that the use of digital games in learning can improve social interactions, cooperation, and empathy in children. However, there needs to be supervision and time limits on usage to prevent negative impacts. Keywords: early childhood education, game-based learning, social skills, digital era.